E-HRM USE ON ORGANIZATIONAL PERFORMANCE: A MEDIATION ANALYSIS - Situmorang, Oloan; Mishel (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
People are the most important resource in an organization, agency or company without the human aspect it is difficult for the organization to carry out its mission and objectives. It can also be said that the human factor does not have the karma of the actors or objects that an organization wants to target. The aim of this study was to analyze the influence of e-HRM on organizational performance mediated by employee performance and job satisfaction in PT. Fida Sukses Prosper directly or indirectly. PT. Fida Sukses Makmur is a company engaged in the trade of agricultural products such as garlic, onions, beans and other agricultural products. From the success already achieved, it is not independent of the use of e-HRM that can affect the performance of the organization. This study used data derived from 44 respondents from the results of the dissemination of questionnaires. This study was included in quantitative research using tests conducted in this study were outer model test, inner model test as well as hypothesis testing with SmartPLS 3. The results of this study prove that E-HRM has a positive and significant influence on organizational performance by mediating employee performance and job satisfaction.